2007
DOI: 10.1099/vir.0.82154-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interleukin-15 on CD8+ natural killer cells in human immunodeficiency virus type 1-infected chimpanzees

Abstract: Chimpanzees are susceptible to human immunodeficiency virus type-1 (HIV-1) and develop persistent infection but generally do not progress to full-blown AIDS. Several host and immunological factors have been implicated in mediating resistance to disease progression. Chimpanzees have a higher prevalence of circulating natural killer (NK) cells than humans; however, their role in mediating resistance to disease progression is not well understood. Furthermore, NK cell survival and activity have been shown to be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…This could be an indication that CD8 Ϫ and CD8 ϩ NK cells assume different roles in chimpanzees than in humans. Several studies addressed the role of CD8 ϩ NK cells during HIV-1 infection in chimpanzees and found no decline of these cells (53,55,56). One likely explanation is arguably the observation that the immune pathologies caused by HIV-1 infection in humans vary substantially from those caused by HIV-1 infection in chimpanzees, since HIV-1-infected chimpanzees do not progress to AIDS, although a seminal study demonstrated the development of AIDS in wild chimpanzees infected with naturally occurring chimpanzee simian immunodeficiency virus (SIV cpz ) (57).…”
Section: Cd8mentioning
confidence: 99%
“…This could be an indication that CD8 Ϫ and CD8 ϩ NK cells assume different roles in chimpanzees than in humans. Several studies addressed the role of CD8 ϩ NK cells during HIV-1 infection in chimpanzees and found no decline of these cells (53,55,56). One likely explanation is arguably the observation that the immune pathologies caused by HIV-1 infection in humans vary substantially from those caused by HIV-1 infection in chimpanzees, since HIV-1-infected chimpanzees do not progress to AIDS, although a seminal study demonstrated the development of AIDS in wild chimpanzees infected with naturally occurring chimpanzee simian immunodeficiency virus (SIV cpz ) (57).…”
Section: Cd8mentioning
confidence: 99%
“…The maturation of NK cells is then mainly facilitated by IL-15 [7]- [9] which together with other cytokines such as IL-12 and IL-18, enhances NK cytotoxicity [10] and increases the production of IFN-γ [11] [12]. The subsequent secretion of IFN-α and γ by both NK and T cells represents the key effector functions in the control of viral infection [13] [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IL-15 is more potent than IL-2 in stimulating NK cell function, including secretion of IFN-and of CCR5-binding chemokines [15]. IL-15 has been shown to stimulate the function of immune cells of individuals who are HIV positive, particularly CD8 + memory T cells and NK cell survival and activity [15]. In addition, IL-15 induced increasing antibody-dependent cellular cytotoxicity and complement-dependent lysis of HIV-1 Env-expressing target cells through augmentation of specific IgG levels in immunized mice [16•].…”
Section: Il-15mentioning
confidence: 99%
“…In addition, IL-15 is more potent than IL-2 in stimulating NK cell function, including secretion of IFN-and of CCR5-binding chemokines [15]. IL-15 has been shown to stimulate the function of immune cells of individuals who are HIV positive, particularly CD8 + memory T cells and NK cell survival and activity [15].…”
Section: Il-15mentioning
confidence: 99%